Bioactivities, Biopharmaceutics, and Advanced Drug Delivery Systems of Magnolol - Kotta, Sabna; Eshmawi, Bayan A.; Alahmadi, Amerh Aiad; Aldawsari, Hibah Mubarak; Badr-Eldin, Shaimaa M.; Nair, Anroop B. (Indian Journal of Pharmaceutical Education and Research, 2024)
Magnolia bark is an important food supplement. Magnolol (ML), 3,3′-Neoligna-8,8′-diene-4,4′- diol, is a bioactive phenolic molecule found in the Magnolia family. Advanced Drug Delivery Systems (DDSs) have been able to enhance therapeutic efficacy and reduce adverse effects of plant-derived bioactive. In the first part of the review, the bioactivities, mechanisms, and clinical prospects of ML are described. A brief explanation of the mechanisms of anti-inflammatory, antioxidant, cardiovascular-protective, neuroprotective, and anti-cancer effects of ML is also provided. Later, the detailed biopharmaceutics of ML is described under solubility, dissolution, bioavailability, and pharmacokinetics. The solubility of ML in different media pH is also explained. The bioavailability of pure ML and its pharmacokinetics after parenteral and oral administrations are described. Further, pharmacokinetics after single and multiple doses of ML is also discussed. Finally, the reported advanced DDSs of ML are reviewed critically. Engineered crystals, solid dispersions, microstructures, and nanostructures of ML-loaded DDSs are reviewed.
Keywords: Biopharmaceutics; Drug delivery; Magnolol; Nanostructure; Pharmacokinetics